Evaluation of environmental contamination with Salmonella spp. in a large animal ward at a Veterinary Hospital in Malaysia - De Lima, Alexandria; Khairuddin, Nurul Hayah; Zakaria, Zunita; Othman, Sarah; Khairani-Bejo, Siti (Universiti Putra Malaysia, 2023)
Veterinary hospitals are important locations for various sick and immunocompromised animal patients. These centers may act as reservoirs for nosocomial diseases such as Salmonella infection, one of the most common causes of healthcare-associated infections in veterinary hospitals. The study was performed at the Large Animal Ward (LAW), University Veterinary Hospital, Universiti Putra Malaysia, to assess the environment’s degree of Salmonella spp. contamination. Environmental samples were obtained from various floor and surface areas in the LAW using sterile, moistened gauze. Salmonella spp. was determined using conventional bacteriological culture on all samples. Positive Salmonella isolates were subject to antimicrobial sensitivity testing. A total of 6 out of 135 (4.4%) samples were found to be positive for Salmonella spp., with 5/116 (4.3%) samples obtained from the ward environment and 1/19 (5.3%) obtained from reusable equipment. Antimicrobial sensitivity testing revealed three resistance profiles: all isolates were resistant to penicillin and enrofloxacin, one isolate was resistant to streptomycin, and one was resistant to gentamicin. The results indicate that animal treatment areas within the LAW can become contaminated with Salmonella spp. This study highlights the importance of improving biosecurity programs to prevent nosocomial diseases in patients and the hospital environment.